EFEKTIFITAS PENGGUNAAN MEDIA FILM UNTUK MENINGKATKAN EMPATI SISWA KELAS VII SMP - Auliyah, Alan; Flurentin, Elia (Jurnal Kajian Bimbingan dan Konseling, 2016)
This study aims to determine the effectiveness of the use of film to improving emphaty sevents grade students junior high school. The study design used a quasi-experimental design using the design of one group pretest-posttest design. Subjects in this study were six students who have the lowest levels of emphaty in the classroom. The research instrument used is the scale of emphaty and guidance experiment. The hypothesis testing is using the Wilcoxon test. Wilcoxon test results showed that the difference value (z) is-2.201 with a significance value of 0.028. Significance value less than 0.05, which means that Ho is rejected, so it can be concluded that the use of film is effective to improving emphaty among sevents grade student of junior high school.